Application of the customs reimport procedure in foreign trade transactions - E. A. Lysenko (Вестник университета)
The study relevance of the customs procedure of reimport consists in the absence of a unified approach to its analysis, the lack of systematization of the conditions for its application, resulting in violations of the law on the part of declarants (less than 1 % of the total number of claimed procedures). The purpose of the study is to develop a methodological approach to the economic and statistical analysis of the procedure application of reimport. The tasks that make it possible to achieve this goal were: analysis of the legal basis for the application of the customs procedure of reimport, identification of the stages of the economic and statistical analysis of the procedure implementation and the formulation of conclusions based on the results of this analysis. When solving problems, general scientific methods were used: system analysis, synthesis, comparison, modeling, as well as graphical and statistical methods. As a result of the study, a methodological approach is proposed based on the models’ presentation of placement under the reimport, depending on the previous procedures, with the identification of features and factors affecting the procedure application under study; the conditions for the application of the reimport are systematized to exclude illegal actions in the field of customs; the directions in which violations of customs legislation occur and models are developed to prevent these violations.